A prospective study on emergency laparoscopic or open cholecystectomy in acute cholecystitis in a tertiary care hospital - M. A., Hari Babu; G. S. R., Hareesh; Reddipogu, Praneeth; Nannam, Venkata Ramanaiah (International Surgery Journal, 2019)
Background: Gallstones are among one of the most common diseases affecting the digestive system requiring hospitalisation with a prevalence of 11% to 36%. Until 2 decades ago, patients presenting with acute cholecystitis were treated conservatively and a delayed interval cholecystectomy was performed after 6 weeks, now a days laparoscopic cholecystectomy was gaining popularity in acute cholecystitis. It cannot be said with certainty preoperatively whether the cholecystectomy is going to be easy or difficult. The aim of the study was to evaluate safety and outcomes of emergency laparoscopic or open cholecystectomy in acute cholecystitis. Methods: This is a prospective, observational, single centre study conducted in the Department of General Surgery, S.V. Medical College/ SVRRGG hospital, Tirupati, for a period of one year from the time of approval of IEC. All patients undergoing emergency laparoscopic or open cholecystectomy for acute cholecystitis and its related complications are studied for various clinical, radiological and other variables. Results: Total 100 patients who presented with acute cholecystitis and undergone cholecystectomy are studied. Age, sex, BMI, comorbities, clinical and usg criteria and intra-operative findings and post-operative complications are analysed. Conclusions: Difficult dissection in cholecystectomy can be predicted using pre-operative parameters like increasing age, male gender, multiple attacks in the past, gallbladder wall thickness >3 mm, and presence of pericholecystic fluid. Surgery performed within 72 hrs had good prognosis and few intra op complications due to good place of dissection due to inflammation.